Effect of acupuncture on hot flush and menopause symptoms in breast cancer- A systematic review and meta-analysis. - Tsai-Ju Chien; Chung-Hua Hsu; Chia-Yu Liu; Ching-Ju Fang (PLoS ONE)
Background Many breast cancer patients suffer from hot flush and medical menopause as side effects of treatment. Some patients undergo acupuncture, rather than hormone therapy, to relieve these symptoms, but the efficacy of acupuncture is uncertain. This meta-analysis evaluated the efficacy of acupuncture on hot flush and menopause symptoms in women with breast cancer. Methods A literature search was performed, following the PRISMA Statement and without language restrictions, of 7 databases from inception through March 2017. All selected studies were randomized clinical trials (RCTs) that examined the effect of needle acupuncture on hot flush and menopause symptoms in patients with breast cancer. The methodological quality of these trials was assessed using Cochrane criteria, and meta-analysis software (RevMan 5.2) was used to analyze the data. Results We examined 844 breast cancer patients (average age: 58 years-old) from 13 RCTs. The trials had medium-to-high quality, based on the modified Jadad scale. The meta-analysis showed that acupuncture had no significant effect on the frequency and the severity of hot flush (p = 0.34; p = 0.33), but significantly ameliorated menopause symptoms (p = 0.009). None of the studies reported severe adverse events. Conclusions Acupuncture significantly alleviated menopause symptoms, but had no effect on hot flush. Breast cancer patients concerned about the adverse effects of hormone therapy should consider acupuncture. Further large-scale studies that also measure biomarkers or cytokines may help to elucidate the mechanism by which acupuncture alleviates menopause symptoms in patients with breast cancer.